2015
DOI: 10.15252/emmm.201505256
|View full text |Cite
|
Sign up to set email alerts
|

Impaired GAPDH ‐induced mitophagy contributes to the pathology of Huntington's disease

Abstract: Mitochondrial dysfunction is implicated in multiple neurodegenerative diseases. In order to maintain a healthy population of functional mitochondria in cells, defective mitochondria must be properly eliminated by lysosomal machinery in a process referred to as mitophagy. Here, we uncover a new molecular mechanism underlying mitophagy driven by glyceraldehyde-3-phosphate dehydrogenase (GAPDH) under the pathological condition of Huntington’s disease (HD) caused by expansion of polyglutamine repeats. Expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(119 citation statements)
references
References 87 publications
(114 reference statements)
2
115
1
1
Order By: Relevance
“…In microautophagy, cytoplasmic cargo is directly trapped and engulfed through membrane invagination by lysosomes. Although it is believed to be a random process, recent evidence suggests that parts of mitochondria are also degraded through this mechanism 95 . CMA, on the other hand, specifically degrades cytosolic proteins with a KFERQ motif, by directly transferring them to lysosomes.…”
Section: The Role Of Autophagy During Aging Of the Heartmentioning
confidence: 99%
“…In microautophagy, cytoplasmic cargo is directly trapped and engulfed through membrane invagination by lysosomes. Although it is believed to be a random process, recent evidence suggests that parts of mitochondria are also degraded through this mechanism 95 . CMA, on the other hand, specifically degrades cytosolic proteins with a KFERQ motif, by directly transferring them to lysosomes.…”
Section: The Role Of Autophagy During Aging Of the Heartmentioning
confidence: 99%
“…Mechanistically, iGAPDH signals the induction of direct engulfment of damaged mitochondria into lysosomes. However, expanded polyglutamine repeats (mutant Huntingtin) inhibit GAPDH-induced mitophagy through abnormal interaction with GAPDH [69]. Hwang et al reported a reduction in GAPDH-induced mitophagy in HD cell models due to the inactivation of GAPDH by polyglutamine expansion[69].…”
Section: Mitophagy In Neurodegeneration and Agingmentioning
confidence: 99%
“…This process is mainly triggered by glyceraldehyde-3-phosphate dehydrogenase (GAPDH), that gets inactivated by mHtt and thus losses its selective association with damaged mitochondria. Further, abnormal interaction of mitochondrial GAPDH with mHtt impeded GAPDH-mediated mitophagy, contributing to accumulation of damaged mitochondria and increased cell death [60]. Recent studies have reported that mHtt also curtails the maturation of SREBP and up regulates the expression of LXR and LXR-targeted genes (ABCG1, ABCG4, SREBP, ApoE and HMGCoA reductase) which further lowers both the synthesis and transport of cholesterol from astrocytes to neurons via ApoE [56].…”
Section: Huntington's Diseasementioning
confidence: 99%